A STUDY ON THE LIFE CYCLE OF MEMBER OF THE FAMILY COREIDAE - Varis, Md. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Heteroptera is a large insect suborder with more than 42,300 species divided into seven infraorders and 89 families. Its key families are the Pentatomidae, Coreidae, Lygaeidae, Reduviidae, and Miridae. There are 2201 species in the Coreidae family, divided into 500 genera. Members of this family are phytophagous, which means they eat grains, legumes, cucurbit crops, soft fruits, and nuts. Coreinae, Pseudophloeinae, Meropachydinae, and Agriopocorinae are the four subfamilies of the Coreidae family. Coreinae is found all throughout the globe, although it is most common in the tropics. Pseudophloeinae is mostly found in the Old World. Meropachydinae and Agriopocorinae are uncommon subfamilies with just a few genera identified for each. Insects are one of the most varied animal groups on the world, with over a million identified species accounting for more than half of all living creatures. The number of living insect species is believed to be between six and 10 million, accounting for over 90% of all metazoan life forms on the planet. There are 30 orders in the class Insecta. The Hemiptera order is the biggest and most successful of the hemimetabolous insect orders. Between the larval and adult stages, they do not change. Instead, their young, known as nymphs, are very similar to the adults. In contrast to holometabolous insects, the final transformation involves the development of functional wings and sexual organs with no pupal stage in between. They are classified into two suborders: Heteroptera and Homoptera, which are usually easy to discern.